If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5j + a = t + -2 Reorder the terms: a + 5j = t + -2 Reorder the terms: a + 5j = -2 + t Solving a + 5j = -2 + t Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5j' to each side of the equation. a + 5j + -5j = -2 + -5j + t Combine like terms: 5j + -5j = 0 a + 0 = -2 + -5j + t a = -2 + -5j + t Simplifying a = -2 + -5j + t
| 10x^2+6x=-1 | | 16x-19(x-16)= | | x/-11=-13 | | 2y+3x=44 | | 6+ln(x-5)=8 | | 3/x+1=9/4x+5 | | 53.8-4.8=(0.21) | | 760=40h(200) | | 4z-(2z-5)=3-4(2z+3) | | 21x^2+28x= | | 7/5x-2 | | 9y^2+24y+20=0 | | 3(x-3)-4x=7x+15 | | 154=2x-4(5x-7) | | -13r+5(1-15r)= | | 2y=3x+44 | | 36a^2-12a+1=0 | | 1/2m*2-9n*2-m*2-12+n | | X^2(x-8)+17(x-8)= | | 12x-5=28x+7 | | 5(x-7)+14=2(x-6) | | 2x=3x+44 | | 7x^6-2x^5+x^2+5x+2= | | 4y-12=y+12 | | -1+4+7=2x-9 | | (1/3)p=(1/2)p+(1/3) | | -2/5x=-10 | | 0.4y+0.1y=-2.5 | | 27=30-3(6-2c) | | pi/7=a/4 | | x(6x-11)=-5 | | x/-16=-10 |